The Role of Electronic Service Quality on E-Commerce Services Towards Customer Loyalty - Joshua Enrico Sitompul; Hapsari Setyowardhani (P2M Politeknik Pertanian Negeri Samarinda, 2023)
This study examines the quality of electronic services e-servqual and its impact on electronic service quality, customer loyalty through reuse intention, and word of mouth. The internet has become a bridge or connection that forms an extensive network in the exchange of information, enabling fast data transfer. With the internet, there are no longer boundaries between devices connected to the internet gateway in the global market. The presence of the internet in this global market allows individuals to communicate with others without limitations of time, distance, or boundaries. This has resulted in innovations in the ever-changing and increasingly modern world of transactions. The internet's presence in the global market has fostered communication without knowing boundaries, time, or distance. The impact of globalization enables businesses to expand both domestically and globally. Traveloka is a digital business application that caters to various needs in a location. The method used in this study is quantitative and employs purposive sampling. A total of 251 respondents, who are users of the Traveloka application, were processed using SmartPLS. The results indicate that all indicators of the six dimensions of the E-Servqual variables significantly and positively influence electronic customer satisfaction. One dimension, user-friendliness, has a more significant impact. Additionally, electronic customer satisfaction affects reuse intention and word of mouth. The data required for this study could be better because nearly half of the respondents are teenagers or adults who have used the Traveloka application for less than three years.